Survival of Older Patients With Advanced CKD Managed Without Dialysis: A Narrative Review - Angela Chou; Kelly Chenlei Li; Mark Ashley Brown (Kidney Medicine, 2022)
Shared decision making is important when deciding the appropriateness of dialysis for any individual, particularly for older patients with advanced chronic kidney disease who have high mortality. Emerging evidence suggests that patients with advanced age, high comorbidity burden, and poor functional status may not have any survival advantage on dialysis compared with those on a conservative kidney management pathway. The purpose of this narrative review is to summarize the existing studies on the survival of older patients with stage 4 or 5 chronic kidney disease managed with or without dialysis and to evaluate the factors that may influence mortality in an effort to assist clinicians with shared decision making. Median survival estimates of conservative kidney management patients are widely varied, ranging from 1-45 months with 1-year survival rates of 29%-82%, making it challenging to provide consistent advice to patients. In existing cohort studies, the selected group of patients on dialysis generally survives longer than the conservative kidney management cohort. However, in patients with advanced age (aged ≥80 years), high comorbidity burden, and poor functional status, the survival benefit conferred by dialysis is no longer present. There is an overall paucity of data, and the variability in outcomes reflect the heterogeneity of the existing studies; further prospective studies are urgently needed.